Preferensi Konsumen Tentang Kualitas Produk dan Layanan di Kafe Tematik (Studi Kasus di Bangkalan) - Fadilah, Nur; Firmansyah, Raden Arief; Maflahah, Iffan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
One of the causes of the increasing number of café is the viral 3F phenomenon. This condition increases competition between other cafés. Assessment of customer satisfaction could be an effort to design a marketing strategy to ensure business sustainability. This study aims to determine customer satisfaction and the importance of customer parameters regarding product and service quality, particularly theme café cases. Data was collected by questionnaire using nonprobability sampling and purposive sampling. Data was analyzed to assess customer satisfaction using the CSI method, the priority attributes were determined by the PGCV method, and IPA assessed the determination of the most priority attribute. The CSI result showed customer satisfaction on level satisfy. In detail, CSI for product attributes was 72.73% in population A and 73.71% in B. Meanwhile, for service quality, CSI at populations A and B was 77.84% and 78.41%, respectively. A total of 5 of the most priority attributes were to be enhanced based on PGCV and IPA results. For product quality, i.e., conformity between food quality and price (P4), conformity between food price and portion (P5) and conformity between food price and taste (P6). Meanwhile, the most prioritized improvement was the cleanliness and neatness of the café (S4) and order response time (S18).